Meningkatkan Kemampuan Kognitif Anak Melalui Permainan Puzzle Huruf Hijaiyah - Rohimah Hasibuan (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to determine the improvement of children’s cognitive development in pronouncing and recognizing hijaiyah letters through the use of hijaiyah letter puzzle media at PAUD Ummi, Teluk Binjai Village, Kualuh Hilir Subdistrict, North Labuhanbatu Regency. This research is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of four stages, namely planning, implementation, observation, and reflection. The research subjects were 20 children aged 5-6 years, consisting of 12 girls and 8 boys. Data collection techniques were carried out through observation of children’s ability to pronounce and recognize hijaiyah letters. The results of the study show an improvement in children’s abilities in each cycle. In the pre-cycle stage, 15 children (75%) were in the Developing Beginning (MB) category, 5 children (25%) were in the Developing as Expected (BSH) category, and none of the children reached the Very Well Developed (BSB) category. In Cycle I, the number of children in the BSH category increased to 10 children (50%), while 4 children (20%) reached the BSB category, and 6 children (30%) were still in the MB category. Furthermore, in Cycle II there was a significant improvement, where 5 children (25%) were in the BSH category and 15 children (75%) had reached the BSB category. Thus, the use of hijaiyah letter puzzle media has been proven to improve children’s cognitive abilities in pronouncing and recognizing hijaiyah letters in early childhood education.